The ancestor : a novel - Trussoni, Danielle (William Morrow, an imprint of HarperCollinsPublishers, 2020)
"It feels like a fairy tale when Alberta 'Bert' Monte receives a letter addressed to 'Countess Alberta Montebianco' at her Hudson Valley, New York, home that claims she's inherited a noble title, money, and a castle in Italy. But her ancestry has a dark side, and Bert soon learns that her family history is particularly complicated. As Bert begins to unravel the Montebianco secrets, she begins to realize her true inheritance lies not in a legacy of ancestral treasures, but in her very genes."--Provided by publisher.